Household sanitation and hygiene practices of BRAC member and non-member households: evidences from Matlab, Bangladesh - Ahmed, Syed Masud; Chowdhury, Mushtaque; Bhuiya, Abbas (BRAC Research and Evaluation Division (RED), 2020)
Provision of potable water and sanitation facilities for the vast majority of the poverty-stricken people of developing countries remains a formidable challenge for sustainable development To accomplish this task, policy makers agree that water and sanitation should be a task of the people with government participation rather than being a task of the government with people's participation. The health benefits resulting from improved sanitation and water supplies will be limited if behaviour modification does not occur simultaneously. NGOs can play a significant role in this :field. BRAC's EHC integrates preventive health inputs with RDP's mainstream activities in a comprehensive package. We tried to see how these activities translate into desirable health behaviour among beneficiary households by comparing them with households of a similar socioeconomic status but not receiving these inputs.